Bamboo Leaf Sign as a Sensitive Magnetic Resonance Imaging Finding in Spinal Subependymoma: Case Report and Literature Review - Hiroyuki Toi; Yukari Ogawa; Keita Kinoshita; Satoshi Hirai; Hiroki Takai; Keijiro Hara; Nobuhisa Matsushita; Shunji Matsubara; Masaaki Uno (Case Reports in Neurological Medicine)
Background and Importance. Subependymoma occurs very rarely in the spinal cord. We report another case of spinal subependymoma along with a review of the literature and discussion of a radiological finding that is useful for preoperative diagnosis of this tumor. Clinical Presentation. A 51-year-old man presented with a 2-year history of progressive muscle weakness in the right lower extremity. Sagittal magnetic resonance imaging (MRI) showed spinal cord expansion at the Th7–12 vertebral level. Surgical resection was performed and the tumor was found to involve predominantly subpial growth. Histological diagnosis was subependymoma, classified as Grade I according to criteria of World Health Organization. We made an important discovery of what seems to be a characteristic appearance for spinal subependymoma on sagittal MRI. Swelling of the spinal cord is extremely steep, providing unusually large fusiform dilatation resembling a bamboo leaf. We have termed this characteristic MRI appearance as the “bamboo leaf sign.” This characteristic was apparent in 76.2% of cases of spinal subependymoma for which MRI findings were reported. Conclusion. The bamboo leaf sign on spinal MRI is useful for differentiating between subependymoma and other intramedullary tumors. Neurosurgeons encountering the bamboo leaf sign on spinal MRI should consider the possibility of subependymoma.